Pulmonary Rehabilitation Accelerates the Recovery of Pulmonary Function in Patients With COVID-19 - Zhu, Pengfei; Wang, Zhengchao; Guo, Xiaomi; Feng, Zhiyong; Chen, Chaochao; Zheng, Ai; Gu, Haotian; Cai, Yu (Frontiers in Cardiovascular Medicine, 2021)
Objectives: To evaluate the effect of in-hospital pulmonary rehabilitation (PR) on short-term pulmonary functional recovery in patients with COVID-19. Methods: Patients with COVID-19 (n = 123) were divided into two groups (PR group or Control group) according to recipient of pulmonary rehabilitation. Six-min walk distance (6MW), heart rate (HR), forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1), diffusing capacity of the lung for carbon monoxide (DLCO), and CT scanning were measured at the time of discharge, 1, 4, 12, and 24 weeks. Results: At week one, both PR group and Control group showed no significant changes in pulmonary function. At 4 and 12 weeks, 6MW, HR, FVC, FEV1, and DLCO improved significantly in both groups. However, the improvement in the PR group was greater than the Control group. Pulmonary function in the PR group returned to normal at 4 weeks [FVC (% predicted, PR vs. Control): 86.27 ± 9.14 vs. 78.87 ± 7.55; FEV1 (% predicted, PR vs. Control) 88.76 ± 6.22 vs. 78.96 ± 6.91; DLCO (% predicted, PR vs. Control): 87.27 ± 6.20 vs. 77.78 ± 5.85] compared to 12 weeks in the control group [FVC (% predicted, PR vs. Control): 90.61 ± 6.05 vs. 89.96 ± 4.05; FEV1 (% predicted, PR vs. Control) 94.06 ± 0.43 vs. 93.85 ± 5.61; DLCO (% predicted, PR vs. Control): 91.99 ± 8.73 vs. 88.57 ± 5.37]. Residual lesions on CT disappeared at week 4 in 49 patients in PR group and in 28 patients in control group (p = 0.0004). Conclusion: Pulmonary rehabilitation could accelerate the recovery of pulmonary function in patients with COVID-19.